(untitled) (Vietnam Journal of Community Medicine, 2026)
Objevtive: Evaluating the effectiveness of gap-PCR combined with MALDI-TOF testing technique in detecting thalassemia carriers among pregnant women compared with red blood cell indices and hemoglobin electrophoresis. Methods: A cross-sectional design was conducted on 476 pregnant women from January to October 2025. Participants underwent parallel screening using the traditional method (hematology indices and hemoglobin electrophoresis) and genetic testing with gap-PCR combined with MALDI-TOF. Results: A total of 56/476 (11.8%) carriers were detected, including 7.6% alpha, 3.8% beta, and 0.4% combined alpha-beta mutations. Sensitivity and specificity of the traditional method were 92.9% and 86.7%, respectively, with PPV 48.1% and NPV 98.9%. Gap-PCR combined with MALDI-TOF demonstrated superior sensitivity (98.2%) and specificity (100%), with PPV 100% and NPV 99.8%. Conclusion: Gap-PCR combined with MALDI-TOF provides high diagnostic accuracy and enables one-step screening, improving the efficiency of thalassemia carrier detection.